PENGARUH INTERVENSI MAKANAN KUDAPAN TERHADAP PENINGKATAN KADAR GLUKOSA DARAH DAN DAYA INGAT ANAK SEKOLAH DASAR - Lilik Kustiyah; Hidayat Syarief; Hardinsyah Hardinsyah; Rimbawan Rimbawan; Sri Hartati Suradijono (Media Gizi dan Keluarga, 2006)
ABSTRACT. The objective of this study was to analyze the effect of snack intervention on blood glucose level and memory improvement ofelementary school's students, Subjects of this study were 184 students offour (4) elementary schools (grade 6, 5 and 4) at Bogor District, West Java. The study employed a quasi-experimental design and followed experimental procedures to control the subject's food intake and motoric activity during the study period At the day of intervention, both control and intervention's subjects were ordered not to have breakfast at home. Intervention's subjects were provided with snack (buras, at 10.00 AM) which contained 381.7 kcal energy and 5 g protein, but control's subjects were not. Two types ofpsychological test (word andfigure) were applied twice (at 09.00 and 11.00 AM). Then, at the same time, subject's blood was taken to determine blood glucose, haemoglobin, and hematocrite levels. Interviews with subjects and their mothers were carried out to collect socioeconomic data and dietary intake. Result of the study indicated that snack intervention increased significantly (p<O.OI) blood glucose level (20.8 mgld/) approximately 1 hour after snack given. Blood glucose level significantly (p<O.OI) affected the word's and figure's memory performance. The higher the blood glucose level the better the memory performance. Keywords: Snack intervention, blood glucose level, memoryperformance, Elementary School Students